Cultural distinctions between the countries and differences in level of development of regions in the same country: what it is more important for sales on B2B markets - Klimin, Anastasii
Rozdielnosť kultúry medzi krajinami a jej vzťah k rozdielnosti úrovne sociálneho a makroekonomického rozvoja regiónov v tej istej krajine.